PLACE AND VALUE OF ENDOVASCULAR AND HYBRID TECHNOLOGIES IN TREATMENT OF LOWER EXTREMITY PERIPHERAL ARTERY DISEASE - KH.S. MUKHAMMADIEVA; A.D. GAIBOV; A.K. BARATOV; E.L. KALMYKOV; O. NEMATZODA; D.A. RAHMONOV (Avicenna Tajik State Medical University, 2018)
Objective: The article analyzed the possibilities of hybrid and endovascular operations in the treatment of patients with chronic ischemia of the lower limbs. The analysis of the literature shows that at the present stage these interventions are being applied more and more often, often being an alternative to traditional operations. Most researchers have proven that when performing hybrid and endovascular operations, a low incidence of cardiovascular events and infectious complications is noted, and in most cases, it is possible to save the limb. However, the effectiveness of this or that method of treating peripheral artery disease of the lower limbs depends both on the degree of limb ischemia and anatomical level of the lesion where performed revascularization. To date, the literature on this issue does not have a definitive answer regarding the priority in choosing the method of revascularization of the limb. This is primarily due to the type of arterial lesion, the level of occlusion or stenosis, and the presence of severe comorbid status, the experience of the surgeon and the technical equipment of the clinic.